Targeted sequencing of plasma cell-free DNA to predict response to PD1 inhibitors in advanced non-small cell lung cancer. (November 2019) - Guibert, Nicolas; Jones, Greg; Beeler, John F.; Plagnol, Vincent; Morris, Clive; Mourlanette, Jean; Delaunay, Myriam; Keller, Laura; Rouquette, Isabelle; Favre, Gilles; Pradines, Anne; Mazieres, Julien
Highlights: Targeted (36 genes) plasma NGS was performed in 86 patients treated with ICI. Combination of molecular determinants of response to ICI can predict outcomes. Early changes (1 month) in ctDNA burden also predict sustained responses. Abstract: Objectives: Tumor mutational burden is an emerging biomarker of response to immune checkpoint inhibitors (ICI), whose clinical adoption is challenging. We hypothesized that targeting limited but relevant genetic alterations in plasma cell-free DNA along with early monitoring may non-invasively predict response to ICI in advanced non-small cell lung cancer (NSCLC). Material and methods: Plasma samples from patients with progressive NSCLC collected before ICI initiation and at 1 month were profiled from responders (R: PFS > 6 months) and non-responders (NR: progressive disease at first evaluation) using amplicon sequencing of hotspots and coding regions from 36 genes. The molecular profile of ctDNA, and its early kinetics were analyzed. Results: 97 patients were analyzed, of which 86 (39 R, 47 NR) were evaluable. Alterations in ctDNA were detectable in 67/86 baseline samples (78%). The detection of a targetable oncogenic driver was associated with a 2 months PFS. The presence of a PTEN or STK11 mutation was correlated with early progression (HR 8.9, p = 0.09 for PTEN, HR 4.7, p = 0.003 for STK11 ), while transversion mutations (Tv) in KRAS and TP53 predicted better outcomes (HR 0.36, p = 0.011 for TP53 Tv; HR 0.46, p = 0.11 for KRAS Tv). Patients with a low "immune score" (driver and/or PTEN or STK11 mutation and/or without KRAS or TP53 Tv) derived poor outcomes (median PFS 2 months), compared with patients with a high immune score (no driver, no PTEN or STK11 and with KRAS or TP53 Tv (median PFS 14 months, p = 0.0001, HR 2.96). Early changes in the ctDNA allele fraction (AF) of 65 specimens were correlated with clinical outcomes (14 months PFS if AF decreases vs. 2 months if AF increases, p < 0.0001). Conclusion: Targeted sequencing of plasma ctDNA and monitoring its early variations can predict response to ICI.